Acupuncture for emotional disorders in patients with migraine: a systematic review protocol. Issue 1 (6th January 2020) - Sun, Ning; Sun, Mingsheng; Li, Zhengjie; Sun, Rui-Rui; Zhao, Ling; Chen, Jiao; Liang, Fan-rong
Abstract : Introduction: Migraine is the second-leading cause of years lived with disability worldwide. The high prevalence of migraine-related emotional disorders is often overlooked. Acupuncture is often used to treat both migraine and emotional disorders. This systematic review protocol aims to analyse whether acupuncture is effective for treating emotional disorders in patients with migraine. Methods and analysis: Nine databases will be searched from inception to may 2019: cochrane central register of controlled trials, medline, embase, allied and complementary medicine database, cinahl, china national knowledge infrastructure, chinese biomedical literature database, vip database and wanfang database. Randomised controlled trials (rcts) of acupuncture therapy for migraine with emotional functioning outcomes, which were reported in chinese or english, will be included. The primary outcome is the change in emotional functioning. Study selection, data extraction and assessment of the risk of bias will be performed independently by two or more reviewers. Revman software (v.5.3) will be used to perform the assessment of the risk of bias and data synthesis. Ethics and dissemination: Ethics approval is not be needed because the data will not contain individual patient data, and there are no concerns about privacy. The results of this meta-analysis will be disseminated through publication in a peer-reviewed journal or relevant conference. Trial registration number: CRD42019139433.